PEMBATALAN DESAIN INDUSTRI KARENA ALASAN MEMPUNYAI PERSAMAAN PADA POKOKNYA - Dewi Susiana (PREMISE LAW JURNAL, 2013)
Design Industry in Indonesia is regulated by law No. 31/2000. To obtain legal protection an industrial design must be registered, but an industrial design that has been registered can also be canceled. There are several factors that caused the cancellation of the industrial design were as follows: the registration of the industrial design was not substantively exaimined, the novelty in an industrial deisgn was not fulfilled, and there was no explanation of similarity in Law No. 31/2000 on Industrial Design. The results of the research showed that the term ‘similar’ can be interpreted as the element which does not have significant differences, either in its form, configuration, line composition and color, or the combination of them. Keywords: Cancellation of Industrial Design,  Similarity in Its Principle